البلى اللفظي ماهيته وحدوده وآراء اللغويين العرب في بيانه - بدر عبد الستار البدر عبير (Journal of College of Education, 2018)
Verbal deterioration words is one of the aspects that show the development and vitality of languages . this is due to the fact that such words are exposed to be cut off their ends by being over used , this leads to special deviations that are controlled by different elements.